ANALISIS TINGKAT UTILITAS SISTEM ANTRIAN MODEL M/M/S PADA PROSES TRANSAKSI DI PT BANK RAKYAT INDONESIA (PERSERO) TBK KANTOR CABANG SIDRAP UNIT PANGKAJENE - Nuryadin, Rusmin; Pebriani, Emylia (Universitas Muhammadiyah Parepare, 2020)
The objective of this research to analyze and find out the Utility Level of M / M / S Models in the Transaction Process at PT Bank Rakyat Indonesia (Persero) Tbk, Pangkajene Unit, Sidrap Branch Office. The technique of collecting data using observation, interviews, and documentation. In this study, the data analysis technique used is the M / M / S Model which has two or more service channels/systems available to serve the customers who come. The results show that the model of PT. Bank Rakyat Indonesia Persero Tbk Pangkajene Sidrap Branch Office Unit is a type of Multi-Channel - single Phase model by implementing queuing discipline namely FIFO.